Off-ice fitness of elite female ice hockey players by team success, age and player position - Ransdell, L. B.; Murray, T. M.; Gao, Y. (The Journal of Strength and Conditioning Research, 2013)
This study examined off-ice fitness profiles of 204 elite female ice hockey players from 13 countries who attended a high-performance camp organized by the International Ice Hockey Federation (IIHF) in Bratislava, Slovakia, in July of 2011. Athletes were tested using standardized protocols for vertical jump (centimeters), long jump (centimeters), 4-jump average (centimeters), elasticity ratio (4-vertical jump average/vertical jump), pull-up or inverted row (n), aerobic fitness (VO2max), body mass (kilograms), and body composition (% fat). These variables were examined relative to team success in major international hockey competition (group 1: Canada and USA, group 2: Sweden and Finland, group 3: All other participating countries), age group (Under 18 and Senior/Open Levels), and player position (forwards, defenders, and goalies). The athletes from countries with the best international records weighed more, yet had less body fat, had greater lower body muscular power and upper body strength, and higher aerobic capacity compared with their less successful counterparts. Compared with the younger athletes, athletes from the senior-level age group weighed more and had higher scores for lower body power, pull-ups, and aerobic capacity. There were no significant differences in anthropometric or fitness data based on player position. This study is the first to report the physical characteristics of a worldwide sample of elite female ice hockey players relative to team performance, age, and player position. Coaches should use these data to identify talent, test for strengths and weaknesses in conditioning programs, and design off-ice programs that will help athletes match the fitness profiles of the most successful teams in the world.